Genomic disruption of the histone methyltransferase SETD2 in chronic lymphocytic leukaemia - Parker, H; Rose-Zerilli, M; Larrayoz, M; Clifford, R; Edelmann, J; Blakemore, S; Gibson, J; Wang, J; Ljungström, V; Wojdacz, T; Chaplin, T; Roghanian, A; et al. (Nature Publishing Group, 2016)
Histone methyltransferases (HMTs) are important epigenetic regulators of gene transcription and are disrupted at the genomic level in a spectrum of human tumours including haematological malignancies. Using high-resolution single nucleotide polymorphism (SNP) arrays, we identified recurrent deletions of the SETD2 locus in 3% (8/261) of chronic lymphocytic leukaemia (CLL) patients. Further validation in two independent cohorts showed that SETD2 deletions were associated with loss of TP53, genomic complexity and chromothripsis. With next-generation sequencing we detected mutations of SETD2 in an additional 3.8% of patients (23/602). In most cases, SETD2 deletions or mutations were often observed as a clonal event and always as a mono-allelic lesion, leading to reduced mRNA expression in SETD2-disrupted cases. Patients with SETD2 abnormalities and wild-type TP53 and ATM from five clinical trials employing chemotherapy or chemo-immunotherapy had reduced progression-free and overall survival compared with cases wild type for all three genes. Consistent with its postulated role as a tumour suppressor, our data highlight SETD2 aberration as a recurrent, early loss-of-function event in CLL pathobiology linked to aggressive disease.Leukemia advance online publication, 10 June 2016; doi:10.1038/leu.2016.134.